Europeans See NATO as Only Real Guarantor of Security. - United States. Department of State. Office of Research.; Carriere, Erin.; Dean, Anna. (Tufts University. Tisch Library., 2019)
Public and elite support for membership in NATO is currently strong in both the newer and older NATO member states. However, Office of Research mass public and elite surveys along with focus groups in capital cities suggest that this support is not without cracks. An integrated analysis of findings from these surveys and focus groups yields the following key findings [...].; Opinion Analysis M-100-04